Entrepreneurship Training on Beverage Innovation for Students of Al-Azhar Private Senior High School Batam: Product Creation and Selling Price Calculation - Alhamdi, Rezki; Saputra, Eryd; Pratama, Tito; Thandzir, Moh; Sipayung, Natal Olotua; Rais, Syafruddin; Irwansyah, Syailendra Reza Irwansyah; Ilham, Wahyudi; Maldin, Siska Amelia; yusuf, Abd Rahman (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This community service program was designed to develop entrepreneurial skills and financial literacy among high school students through practical training on beverage product creation and selling price calculation. The activity was conducted at Al-Azhar Private Senior High School Batam by lecturers and students of Batam Tourism Polytechnic. The training introduced participants to basic entrepreneurship concepts, production processes of contemporary beverages, cost management, and pricing strategies. Using a combination of lectures, demonstrations, and hands-on practice, students were guided to produce beverage products and calculate their unit costs and profit margins. The results revealed a significant improvement in students’ understanding of cost calculation, creativity in product development, and motivation toward entrepreneurship. The training not only enhanced practical skills but also inspired students to consider business opportunities in the food and beverage sector. This program serves as a sustainable model for vocational and entrepreneurial education in secondary schools